BLDC PROTOTYPE DESIGN FOR HYBRID SCOOTER CONVERSION KIT - Hidayat Tullah Muhammad; D.A. Sumarsono; Fuad Zainuri (Sekolah Tinggi Teknologi Wastukancana, 2023)
This study aims to develop a BLDC design which is the main component in the conversion of a hybrid scooter motorcycle. The 1KW BLDC motor is designed as a plug-in powertrain embedded in the rear wheel of the scooter which aims to convert the powertrain from the Internal Combustion Chamber (ICE) to a Hybrid ICE-Electric. The BLDC motor is designed based on the results of field observations to be embedded in a scooter motor with a capacity of 110-150cc, with the appropriate BLDC motor specifications being 1000W power, 48VDC working voltage with a maximum rotational speed of 500Rpm. The next stage in the BLDC design is to determine the number of magnetic poles (poles) for the rotor, calculate the number of coils for the stator and cable specifications related to the required electric current. The results obtained from this study are the BLDC design for the conversion of a hybrid scooter with specifications of 1000W 48VDC 520Rpm, 11 pole-pairs rotor with a magnetic flux of 0.00024 weber, 18 stator coils with 589 turns of 1mm copper wire, and a strong current of 14.49A. Based on theoretical calculations, the BLDC motor will be able to produce a torque of 13.52 Nm.